2006
DOI: 10.1037/0002-9432.76.3.346
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and well-being of Latina and non-Latina white mothers of youth and adults with an autism spectrum disorder: Cultural attitudes towards coresidence status.

Abstract: This article examined the emotional well-being of 108 Latina and non-Latina White mothers who were coresiding with a youth or adult with an autism spectrum disorder (ASD). It was hypothesized that Latina mothers would be more satisfied with coresidence than non-Latina White mothers, and that satisfaction with coresidence would mediate the relationship between ethnicity and outcomes. When controlling for demographic characteristics, non-Latina White mothers were more distressed and had lower levels of psycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 37 publications
2
54
0
1
Order By: Relevance
“…The impact of caring for a child with autism on the mental health of caregivers has been well documented (Abbeduto et al 2004;Magana and Smith 2006;Smith et al 2008). Given the mental health impact of caregiving on mothers, it was not surprising to see female caregivers of children with autism in our study to have lower mental HRQOL than US norms.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The impact of caring for a child with autism on the mental health of caregivers has been well documented (Abbeduto et al 2004;Magana and Smith 2006;Smith et al 2008). Given the mental health impact of caregiving on mothers, it was not surprising to see female caregivers of children with autism in our study to have lower mental HRQOL than US norms.…”
Section: Discussionmentioning
confidence: 57%
“…Several studies have documented the occurrence of negative outcomes such as stress, anxiety, and depression among caregivers of children with autism (Abbeduto et al 2004;Bouma and Schweitzer 1990;Davis and Carter 2008;Kasari and Sigman 1997;Magana and Smith 2006;Smith et al 2008). In their study of well-being among mothers of toddlers and adolescents with autism, Smith et al (2008) found that more than one-third of mothers had scores on a depression scale higher than the clinical cut-off.…”
Section: Introductionmentioning
confidence: 95%
“…Twoy et al (2007) soulignent une plus grande capacité de recadrage chez les parents asio-américains que chez les parents euro-américains, avec un plus grand recours au soutien spirituel chez les parents d'origine asiatique. Comparant la détresse psychologique de parents d'origines hispanique et euro-américaine, Magana et al (2006) montrent que le groupe hispanique présente une détresse psychologique moins importante, associée à une plus grande satisfaction des parents dans la cohabitation avec leur enfant autiste. Ces études indiquent que la différence culturelle ne peut être considérée seulement comme un facteur de risque, et qu'il est nécessaire d'examiner pour chaque groupe immigrant ou minoritaire quels sont les facteurs spécifiques de fragilité ou de résilience.…”
Section: Résumé De L'articleunclassified
“…The Hispanic (Latino) population continues to be the most common culture entering the U.S. Magana and Smith (2006) found that Latina mothers co-residing with their child with disabilities had lower levels of education, were in poorer health, and had more depressive symptoms. According to McHatton and Correa (2005), single Latina mothers lacked language proficiency which affected the women's ability to respond to situations in a more assertive manner.…”
Section: Multicultural Issues In Educating Students With Autismmentioning
confidence: 99%
“…Studies have shown that the maladaptive behaviors of students with autism are more pronounced compared to other developmental disabilities (Dahle & Gargiulo, 2004;Magana & Smith, 2006;Smith, 2004;Winter-Messiers, 2007). Parents of children with autism are more likely to have poorer quality relationships than parents of children with other developmental disabilities (Magana & Smith).…”
Section: Multicultural Issues In Educating Students With Autismmentioning
confidence: 99%